Corporate Governance and Firm Value: The Moderating Effect of Board Gender Diversity - Siong Chin, Yeoh; Ganesan, Yuvaraj; Pitchay, Anwar Allah; Haron, Hasnah; Hendayani, Ratih (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2s (2019): Special Issue: Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, 2019)
The purpose of this research is to examine the relationship between corporate governance and firm value. The component of corporate governance is board size, board independence, number of board monitoring committees, risk management committee. Board gender diversity will be introduced in this study as a moderator variable between corporate governance and firm value. This study adopts a quantitative approach and cross-sectional design. A total of 120 top market capitalization was selected for companies listed in Bursa Malaysia and relevant data are extracted from respective companies’ annual reports. Result shows that board size and board independence are positively significant to firm value. However, board monitoring committee and risk management committee do not show any significant relationship with Tobin's Q. Board gender diversity, however, do not function as a moderating role in the relationship of corporate governance and business performance. This study contributes by explaining the relationship between corporate governance and firm value in a developing country. Policymakers and academician will be able to have a better insight into the research and this study pioneer to test the moderating effect of board gender diversity, and the relationship between risk management committee and firm value. Further this paper, able to enhance knowledge and understanding of relevant authority and help them to strategies new policy or standards for listed company.   Research paper  Keywords: Corporate Governance, Firm Values, Firm Size, Gender, Tobin Q, Board Reference to this paper should be made as follows: Chin, Y. S., Ganesan, Y., Pitchay, A. A., Haron, H., & Hendayani, R. (2019). Corporate Governance and Firm Value: The Moderating Effect of Board Gender Diversity, Journal of Entrepreneurship, Business and Economics , 7 (2s), 43–77.